I35 Substance abuse leads to earlier age of onset of huntington's disease: an epidemiological study of the Enroll-HD database. (13th September 2016) - Schultz, Jordan; Nopoulos, Peg; Moser, David; Paulsen, Jane; Kamholz, John
Abstract : Background: The primary determinant of age of motor onset (AMO) for patients with Huntington's disease (HD) is the number of CAG repeats within the HTT gene. However, environmental factors may also influence the disease course. Identification of these factors could provide strategies to delay disease onset. Aims: The aim of this study was to investigate the relationship between substances of abuse and AMO in patients with HD. Methods: This was a retrospective, epidemiological, observational study of the Enroll-HD database. Participants with motor-manifest HD (n = 2314) were considered for inclusion into one of three substance abuse groups: 1) tobacco abuse at baseline, 2) history of alcohol abuse in the past or at baseline, and 3) past or current use of drugs of abuse. A fourth group of participants that had never abused substances served as a control group. The primary outcome measure was the mean difference in AMO of participants in the substance abuse groups versus the control group, using CAG repeat length as a covariate. Results: The AMO was earlier for participants in the tobacco (n = 581), alcohol (n = 381), and drug abuse groups (n = 230) compared to the control group (n = 751) by 2.5 [F(1, 1296) = 37.3, p < 0.0001], 1.2 [F(1, 1096) = 5.5, p = 0.019], and 3.9 [F(1, 945) = 39.7, p < 0.0001] years, respectively. In all substance abuse groups, the AMO was lowered to a greater degree in females than it was in males. Conclusions: Substances of abuse dramatically decreased the AMO in patients with HD. There are currently no disease-modifying therapies available for patients with HD. However, these findings give providers a simple intervention to recommend to pre-motor manifest patients that could add years without motor symptoms to their lives.